Lambda Carrageenan Displays Antiviral Activity Against the Infectious Pancreatic Necrosis Virus (Ipnv) by Inhibiting Viral Replication and Enhancing Innate Immunity in Salmonid Cells - Sandino-Garcia, A; Imarai-Bahamonde, C; Moenne-Munoz, A; Valdes-Parra, N; Espinoza-Majmud, D (Elsevier B.V., 2024)
Sulfated polysaccharide lambda carrageenan (λ-CGN) was evaluated for its antiviral effect against IPNV using the in vitro infection model of CHSE-214 salmonid cells. A plaque reduction lysis assay revealed that λ-CGN has an IC50 of 0.9 μg⋅mL−1, CC50 > 128 μg⋅mL−1 and a Selectivity Index (SI) > 142. In comparison, iota, kappa carrageenans and lambda oligo-carrageenan (λ-OC) were less effective than λ-CGN against IPNV. λ-CGN showed no virucidal activity when applied directly to viral particles. Time of addition experiments showed that pre-treatment, co-treatment, and post-treatment with λ-CGN significantly reduced viral RNA copies in the cell supernatant. Additionally, a decrease in intracellular viral RNA was observed with pre-treatment and post-treatment, indicating an impact on different stages of viral replication. Polyacrylamide gel electrophoresis of IPNV genomic RNA in presence of λ-CGN showed a reduction in the level of viral genomic RNA. Confocal microscopy confirmed the intracellular localization of λ-CGN, suggesting that λ-CGN may inhibit the synthesis of IPNV genomic RNA. Moreover, cells pre-treated with λ-CGN showed an increased expression of innate immunity genes CXCL11, IL1β, IFNa, and IRF3. These findings highlight the need for further research to confirm the in vivo pharmacological potential of λ-CGN as a new antiviral agent in salmonids. © 2024